Consistent alterations in faecal microbiomes of patients with primary sclerosing cholangitis independent of associated colitis. Issue 5 (28th June 2019) - Rühlemann, Malte; Liwinski, Timur; Heinsen, Femke‐Anouska; Bang, Corinna; Zenouzi, Roman; Kummen, Martin; Thingholm, Louise; Tempel, Marie; Lieb, Wolfgang; Karlsen, Tom; Lohse, Ansgar; Hov, Johannes; et al.
Summary: Background: Single‐centre studies reported alterations of faecal microbiota in patients with primary sclerosing cholangitis (PSC). As regional factors may affect microbial communities, it is unclear if a microbial signature of PSC exists across different geographical regions. Aim: To identify a robust microbial signature of PSC independent of geography and environmental influences. Methods: We included 388 individuals (median age, 47 years; range, 15‐78) from Germany and Norway in the study, 137 patients with PSC (n = 75 with colitis), 118 with ulcerative colitis (UC) and 133 healthy controls. Faecal microbiomes were analysed by 16S rRNA gene sequencing (V1‐V2). Differences in relative abundances of single taxa were subjected to a meta‐analysis. Results: In both cohorts, microbiota composition (beta‐diversity) differed between PSC patients and controls ( P < 0.001). Random forests classification discriminated PSC patients from controls in both geographical cohorts with an average area under the curve of 0.88. Compared to healthy controls, many new cohort‐spanning alterations were identified in PSC, such as an increase of Proteobacteria and the bile‐tolerant genus Parabacteroides, which were detected independent from geographical region. Associated colitis only had minor effects on microbiota composition, suggesting that PSC itself drives the faecal microbiota changes observed. Conclusion: Compared to healthy controls, numerous microbiota alterations are reproducible in PSC patients across geographical regions, clearly pointing towards a microbiota composition that is shaped by the disease itself and not by environmental factors. These reproducibly altered microbial populations might provide future insights into the pathophysiology of PSC.